Post Cesarean Pain Intensity and Wound Healing in ERACS and Conventional Method - Silitonga, Intan Renata; Amalia, Gina (Majalah Kedokteran Bandung, 2024)
Cesarean section is a common delivery method in Indonesia, with a prevalence of 17.6%. This method is used when vaginal delivery is not possible or in emergency cases, in an effort to prevent maternal and infant fatalities. Enhanced Recovery After Cesarean Surgery (ERACS) is a new method whose effectiveness has not been widely studied. The aim of this study was to compare post-cesarean pain intensity and wound healing in patients receiving ERACS and cesarean conventional methods at Bandung Kiwari General Hospital. This cross-sectional study used an analytic observational design and accidental sampling with 52 post-cesarean patients as the subjects during the three-months of study. Pain intensity was observed using the NRS instrument and wound healing was observed using the REEDA scale instrument on days one, two, and six post-surgery. The t-test analysis showed that the ERACS method had better pain intensity post-cesarean than the conventional method with a p-value of 0.000. However, there was no difference in wound healing between ERACS and conventional methods with a p-value of 0.136.